Autologous Myoblasts for the Treatment of Fecal Incontinence: Results of a Phase 2 Randomized Placebo-controlled Study (MIAS). Issue 3 (March 2018) - Boyer, Olivier; Bridoux, Valérie; Giverne, Camille; Bisson, Aurélie; Koning, Edith; Leroi, Anne-Marie; Chambon, Pascal; Déhayes, Justine; Le Corre, Stephanie; Jacquot, Serge; Bastit, Dominique; Martinet, Jérémie; et al.
Abstract : Objective: The aim of this study was to evaluate the efficacy of intrasphincteric injections of autologous myoblasts (AMs) in fecal incontinence (FI) in a controlled study. Summary of Background Data: Adult stem cell therapy is expected to definitively cure FI by regenerating damaged sphincter. Preclinical data and results of open-label trials suggest that myoblast therapy may represent a noninvasive treatment option. Methods: We conducted a phase 2 randomized, double-blind, placebo-controlled study of intrasphincteric injections of AM in 24 patients. The study compared outcome after AM (n = 12) or placebo (n = 12) injection using Cleveland Clinic Incontinence (CCI), score at 6 and 12 months. Patients in the placebo group were eligible to receive frozen AM after 1 year. Results: At 6 months, the median CCI score significantly decreased from baseline in both the AM (9 vs 15, P = 0.02) and placebo (10 vs 15, P = 0.01) groups. Hence, no significant difference was found between the 2 groups (primary endpoint) at 6 months. At 12 months, the median CCI score continued to ameliorate in the AM group (6.5 vs 15, P = 0.006), while effect was lost in the placebo group (14 vs 15, P = 0.35). Consequently, there was a higher response rate at 12 months in the treated than the placebo arm (58% vs 8%, P = 0.03). After delayed frozen AM injection in the placebo group, the response rate was 60% (6/10) at 12 months. Conclusions: Intrasphincteric AM injections in FI patients have shown tolerance, safety, and clinical benefit at 12 months despite a transient placebo effect at 6 months. Abstract : Supplemental Digital Content is available in the text